128k views
0 votes
What is the solution to this system if equations

What is the solution to this system if equations-example-1
User Snorlax
by
8.0k points

1 Answer

2 votes

solution is (x, y ) → (- 1, 4 )

y + 2x = 2 → (1)

y + 4x = 0 → (2)

subtract equation (1) from (2) to eliminate term in y

(y - y ) + (4x - 2x ) = (0 - 2 )

2x = - 2 ( divide both sides by 2 )

x = - 1

substitute x = - 1 in either (1) or (2) and solve for y

(1) → y - 2 = 2 ( add 2 to both sides )

y = 4

solution is (x, y ) → (- 1, 4 )


User Konstantin Paulus
by
7.2k points